Age-Related Variations in Risk Factors, Clinical Presentations, and Coronary Angiographic Outcomes among Female Patients with Acute Myocardial Infarction: A Prospective Observational Study - RAJEEV VERMA, DR RAJEEV VERMA; Ahmad, Dr. Ahtesham; Budhwani, Dr. Priyanka; Srivastava, Dr. Deepak Chandra; Verma, Dr. Manisha (International Journal of Innovative Research in Medical Science, 2024)
Background: Coronary heart disease (CHD) is a leading cause of mortality globally, with acute myocardial infarction (AMI) being a significant contributor. Historically considered a "men's disease," CHD is increasingly diagnosed in women, who often present with atypical symptoms, making diagnosis challenging and leading to suboptimal care. Age-specific differences in risk factors, clinical presentations, and angiographic outcomes in female AMI patients have not been extensively studied. Objective: This prospective observational study aimed to delineate age-related variations in risk factors, clinical presentations, and coronary angiographic outcomes among female patients with AMI, comparing younger (<55 years) and older (≥55 years) age groups. Methods: A total of 115 female patients with AMI were enrolled from December 2018 to November 2020 at Jawaharlal Nehru Medical College and Hospital. Participants underwent coronary angiography, and risk factors such as hypertension, diabetes, dyslipidemia, and smoking were assessed. Statistical analyses included chi-square and Student's t-test. Results: Among the participants, 38 were younger (<55 years) and 77 were older (≥55 years). Dyslipidemia was the most prevalent risk factor in both groups, with significant differences in hypertension (p=0.041), hypothyroidism (p=0.022), and family history of CAD (p=0.003) between age groups. Clinical presentation revealed typical angina as the most common in both age groups, with acute LVF significantly more prevalent in the elderly (p=0.021). Coronary angiography showed high prevalence of significant CAD in both groups, with age-related variations in the extent of disease. Conclusion: This study highlights age-specific differences in risk factors, clinical presentations, and coronary angiographic outcomes among female patients with AMI. These findings underscore the importance of tailored management strategies and targeted interventions for improving outcomes in female AMI patients of different age groups.